The impact of gender equality on the development of education and society (MMIT Proceedings, 2024)
The article is devoted to the study of the relationship between education and gender equality. The article examines various factors influencing the achievement of equality between men and women in the education system, and also suggests promising measures to overcome gender barriers in the educational sphere. The author analyzes the historical aspects and the current state of the problem of gender equality in education, highlights the role of women in this field and their right to equal access to educational resources.